2022
DOI: 10.1111/jfd.13632
|View full text |Cite
|
Sign up to set email alerts
|

Piscirickettsia salmonis forms a biofilm on nylon surface using a CDC Biofilm Reactor

Abstract: Research into Piscirickettsia salmonis biofilms on materials commonly used in salmon farming is crucial for understanding its persistence and virulence. We used the CDC Biofilm Reactor to investigate P. salmonis (LF-89 and EM-90) biofilm formation on Nylon, Stainless steel (316L), Polycarbonate and High-Density Polyethylene (HDPE) surfaces. After 144 h of biofilm visualization by scanning confocal laser microscopy under batch growth conditions, Nylon coupons generated the greatest biofilm formation and coverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 80 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…Despite recent research focused on biofilm formation by P . salmonis ( Vidal et al., 2022 ), the significance of biofilm biology for piscirickettsiosis pathogenesis, as well as for many other aquatic animal diseases, has received little to no attention when compared with its notoriety in field of terrestrial animal diseases ( Clutterbuck et al., 2007 ; Jacques et al., 2010 ). Many studies on bacterial pathogens have reached generalizations on biofilms and their relationship with virulence considering a limited number of traits ( Gajdács et al., 2021 ) and genes ( Wang et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recent research focused on biofilm formation by P . salmonis ( Vidal et al., 2022 ), the significance of biofilm biology for piscirickettsiosis pathogenesis, as well as for many other aquatic animal diseases, has received little to no attention when compared with its notoriety in field of terrestrial animal diseases ( Clutterbuck et al., 2007 ; Jacques et al., 2010 ). Many studies on bacterial pathogens have reached generalizations on biofilms and their relationship with virulence considering a limited number of traits ( Gajdács et al., 2021 ) and genes ( Wang et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rozas-Serri (2022) proposed an interesting conceptual framework for understanding the infectious setting of piscirickettsiosis -P. salmonis mainly exploits skin and gill pathways to invade fish hosts. Later, adhered bacteria can develop microcolony-like aggregates in vivo on the surface of the external epithelial cells of the skin and gills of fish host, as well as on goblet and skeletal muscular cells (Smith et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Isolates of P. salmonis can attach to solid materials and form biofilms in vitro (Levipan et al, 2020; Santibañez et al, 2020). P. salmonis preferentially forms biofilms on Nylon surfaces using a standard ASTM‐approved method and the CDC Biofilm Reactor (Vidal et al, 2022). Additionally, P. salmonis produces a quorum‐sensing signal molecule N‐acetyl‐L‐homoserine lactone, which could be related to the biofilm formation process (Ruiz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we previously reported that this strain generates less biofilm formation compared to the ATCC LF‐89 strain. This also correlates with specific biofilm formation index reported for both genogroups, where a P. salmonis EM‐90‐like strain showed a general temporal decline in the specific biofilm formation index (Vidal et al, 2022). Conversely, other authors described that the biofilms formed by P. salmonis LF‐89 T showed an opposing pattern (Levipan et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, HDPE possesses a smooth surface structure, which have the potential to retard the onset of biofouling and facilitate cleaning (Edwards et al, 2015). Importantly, we recently reported that P. salmonis is capable of forming biofilms on Nylon and HDPE surfaces (Vidal et al, 2022). Thus, the purpose of the current study was to evaluate the effect of FLO, the most commonly antimicrobial used in the aquaculture industry in Chile, in the exposure to and the formation of P. salmonis biofilm on the Nylon and HDPE surfaces, the most common materials used in the fish farmers facilities in the sea water.…”
Section: Discussionmentioning
confidence: 99%